Diverse disability - Richard Berthoud (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Policy has long been based on the assumption that disabled people are either capable, or incapable, of work. This paper extends earlier analyses which show that the probability of employment is a variable, not an absolute. The disability employment penalty varies by number, type, severity and duration of impairments. Many impaired people's job prospects are scarcely affected, and they are probably not "disabled" at all. Others have very low chances of employment, and fit the concept of "incapacity". In between is a group who face serious barriers, without work being ruled out altogether. This "50:50" group may be the primary focus of policy interest.
Keywords: I38; J14; J64; 330; disability; incapacity; labour market; disadvantage